Effect of Triangular Cross-sectional Wedges Inserted into an In-line Tube Bundle on the Tube Deposition - Yisunzam, Pasada; Chinsuwan, Anusorn (Engineering and Technology Horizons, 2020)
The purpose of this study is to investigate the effect of the transverse flow due to the triangular cross-sectional wedges inserted into an in-line bundle. The experiment was carried out on an in-line 6 rows – 3 columns tube bundle. The wedges have the same height with four difference apex angles: 3.58, 7.125, 14.036 and 26.36 degree. The experiment was performed at a constant air velocity and ash concentration of 2.1 m/s, and 0.00365 kg/s, respectively. Four wedge positions from the tube bundle inlet, 7.1%, 29%, 57% and 86% of the tube bundle length, were investigated. It was found that the wedge causes not only the increase in the flow velocity but also the change in flow direction. As a result, the tube deposition was decreased. This effect increases with the apex angle. In addition, the deposition was lowest when the wedges were at the distance of 29% the tube bundle length.